Methodological Bases and Forms of Interrelations of Development of World Economy and Competitiveness of Regional Economy - Egamberdiyev, Farmonqul; Bobokhodjaev, Sarvar; Zakhirova, Gulnora; Olimjanova, Shoira (International Journal of Psychosocial Rehabilitation, 2020)
This article considers the internationalization of production, which is driven by the powerful incentives created by innovation processes, in turn, has an increasingly significant impact on the state and prospects of economic development of individual countries and regions. In the context of globalization, the nature of world economic relations is increasingly changing, which is in fact becoming an integral part of the national process of reproduction, largely defining the characteristics and characteristics of development. The economic dimension of globalization includes the multiplication of cross-sectoral flows of goods and services, capital, labour and information over the past decades, as well as the internationalization of production processes up to the international separation of individual technological operations. Globalization can be characterized as the growing interdependence of national economies, the mutual influence and interaction of different spheres and processes in the world economy, during which an open economy is emerging, and the concept of "open economy" changes as world economic relations develop and strengthen. The main drivers of globalization in the world economy are, above all, fundamental changes in production, which increasingly focus on the world market rather than on the national market. In the context of globalization, the system of international relations is reflected not only in the increase in world trade, but also in the need for international cooperation in all sectors of the economy. Factors such as the development of large multinational companies, the development of scientific and technological progress, the establishment of international and banking systems, the liberalization of the world economy, the progressive development of transnational companies, corporations, holdings, etc., contribute to the development of globalization.